Internalisasi Nilai-Nilai Pendidikan Agama Islam Moderat dalam Membangun Kerukunan Masyarakat Desa Laban Menganti Gresik - Setyawati, Nur Rahayu; Muizzuddin, Muhammad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The concept of religious moderation is an attitude that places diversity as a shared wealth and prioritizes dialogue and harmonious values ​​in social interaction. Moderate Islamic religious education emphasizes the internalization of inclusive, tolerant, and non-exclusive Islamic values ​​so as to encourage the formation of a harmonious and peaceful society. This is very relevant in facing increasingly complex social dynamics in the era of globalization and unlimited information flow. This study aims to describe the process of internalization of moderate Islamic religious education values ​​in building harmony in the Laban Menganti Gresik village community, as well as to analyze the values ​​of moderate Islamic religious education in building harmony in the Laban Menganti Gresik village community. This study is a qualitative research using a case study approach. The data analysis used is the Miles and Huberman model combined with data triangulation. The results of the study indicate that the process of internalizing the values ​​of moderate Islamic religious education in building harmony in the Laban Menganti Gresik village community occurs through several gradual processes consisting of the stages of value transformation, value transactions, and value transinternalization. While the values ​​of moderate Islamic religious education in building harmony in the Laban village community consist of several values, namely: At-Ta'aruf, Tasamuh, tawazun, tawasuth, I'tidal, musyawah, syura. Scientifically, this research can contribute to a broader understanding of tolerance in religion to create harmony, encourage more harmonious relationships, prevent radicalism, and violence in the name of religion